The transfer of knowledge from the MNEs to their Mozambican subsidiaries: A process based on the relationship between source and recipient - Martins, José Duarte Moleiro (2010)
The business opportunities in Southern Africa have originated a growing interest on the part of foreign investors in markets like Mozambique, which is a fact that justifies any effort to learn more about the phenomenon of the transfer of knowledge to the subsidiaries in Mozambique. This study examined four cases with activities in the industrial sector. The results revealed that an efficient transfer of knowledge depends on the source’s ability to transfer this knowledge; the climate of collaboration between the source and the recipient; and the absorptive capacity of the recipient. Under these conditions, the intervention of the expatriates with a profound knowledge of the African reality is essential to create an atmosphere of trust that motivates individuals to acquire, assimilate and explore the new knowledge on the local market.